Applications of contemporary decision-making methods to the development of economy and technology - Liao, Huchang; Xu, Zeshui; Herrera, Francisco (Technological and Economic Development of Economy, 2020)
Applications of contemporary decision-making methods to the development of economy and technology. Technological and Economic Development of Economy, 26(3), pp. 546-548.